DEVELOPING A NEW GENERATION OF SPEECH-LANGUAGE PATHOLOGISTS (SLPs) WITH COMPETENCES IN THE MANAGEMENT OF LITERACY DISORDERS AND LEARNING DISABILITIES IN HONG KONG (Proceedings of International Conference on Special Education, 2015)
One of the recent developments in the education of speech-language pathology is to include literacy disorders and learning disabilities as key training components in the training curriculum. Disorders in reading and writing are so interwoven with disorders in speaking and listening which should be managed holistically, particularly in children and adolescence. With extensive training in clinical linguistics, language disorders, and other theoretical knowledge and clinical skills, speech-language pathologists are the most equipped and competent professionals to screen, identify, diagnose, and manage individuals with literacy disorders. To tackle the challenges and huge demand of services on literacy, language and learning disorders, The Hong Kong Institute of Education has newly developed the Master of Science Programme in Educational Speech-Language Pathology and Learning Disabilities, which is one of the very first speech-language pathology (SLP) training programmes in Asia to blend training components of learning disabilities, literacy disorders and social-emotional- behavioural-developmental disabilities, into the developmental and medical oriented SLP training programme. This new training programme aspires to develop a new generation of SLPs who can offer comprehensive support to individuals with speech, language, literacy, learning, communication and swallowing disorders with different developmental or neurogenic origins, particularly for infants to adolescence, as well as to their family and educational team.